Difficulties in Learning Ukrainian as Foreign Language by the Korean Students on the Intermediate Level - ZBYR, IRYNA (Archives of Business Research, 2020)
The given article highlights certain aspects of teaching Ukrainian as a foreign language to Korean students. Observations and conclusions are made from the author’s own experience. The paper provides answers to significant and topical questions that arise in the learning process; in particular, the author analyzes phonetic, lexical and grammatical difficulties the Korean students face on the intermediate level of learning Ukrainian. The article describes problems and obstacles a teacher and a student has, determines reasons for misusage of language patterns and suggests fresh teaching ideas and ways of their implementation.